Comparison the Autonomic Regional Financial Performance in Southeast Sulawesi Province - Tajuddin Tajuddin; Ilyas Ilyas (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2020)
The consequence of the implementation of regional autonomy is that the regions must have their own abilities to implement government affairs and regional development. There is some research on the financial performance of the area but is still done in a partial autonomic region only. This research compares the financial performance between the autonomic regions of the expansion and the parent area. Based on this, study aims to compare the financial performance of the parent regency and the expanded district. In this study financial performance is measured based on Regional Financial Independence (KKD) rastio, Fiscal Decentralization Degree (DDF) ratio and the Regional Financial Effectiveness Ratio (EKD). Overall, secondary data are used, namely the realization of Regional Original Revenues (PAD), PAD targets, Balancing Funds, Loan Funds, and Regional Expenditures. To answer the research problem, the data is processed using ratio analysis. The results showed that the Regional Financial Performance measured by the ratio of KKD and DDF in the parent regency was still higher than the KKD and DDF in the expanded districts. Both the parent district and the expanded districts of KKD and DDF are included in the Instructive category. The role of the central government is still very dominant in regional financing. In general, the expanded district EKD ratio was very effective while the parent district EKD ratio was generally included in the quite effective category. The financial performance of the regional results is better than the parent region due to the existence of autonomous regions to promote maximum income sources.